MEMECYLON NERVOSUM (MELASTOMATACEAE), A NEW SPECIES FROM SOUTH INDIA - Vadhyar, R. G.; Benjamin, J. H. F.; Sujana, K. A. (Edinburgh Journal of Botany, 2020)
Memecylon nervosum Vadhyar, J.H.F.Benj. & Sujana, a new species of Melastomataceae from the Kanyakumari Wildlife Sanctuary, Western Ghats, India, is described and illustrated. It is compared with the closely allied Memecylon heyneanum Benth. and Memecylon jambosioides Wight.
Keywords: India; Kanyakumari Wildlife Sanctuary; Melastomataceae; Memecylon nervosum